When religion meets mathematics: From mathematical anxiety to mathematical well-being for minority group student - Diponegoro, Ahmad Muhammad; Khalil, Ibrahim Alhussain; Prahmana, Rully Charitas Indra (Jurnal Infinity, 2024)
The mission of positive psychology is to mitigate negative emotions while bolstering positive ones, thereby influencing student engagement in classroom learning activities, including mathematics. This study elucidates the Realistic Mathematics Education (RME) approach within the framework of Islamic teachings—specifically, inheritance law and charity—in the context of fractions and number operations. Its objective is to alleviate mathematics anxiety, a prevalent negative emotion, and enhance well-being during mathematical learning. Drawing upon flow theory from positive psychology, the research endeavors to optimize mathematical well-being by crafting appropriately challenging questions. Employing a descriptive qualitative methodology, the study focuses on an Indonesian mother and her ten-year-old son, residing in Uithoorn, Amsterdam, Netherlands, belonging to minority groups in ethnicity and identity, with religion being a significant aspect of their lives. Data collection involves observation, interviews, tests, and documentation, with analysis employing data reduction, presentation, triangulation, and verification techniques. The study utilizes socio-religious problems as a context, one of the characteristics of RME, such as inheritance division, to design mathematical challenges. The findings demonstrate a marked transition from math anxiety to math well-being, manifested through heightened enthusiasm and cheerfulness in learning mathematics, particularly by the mother. Noteworthy transformations include increased engagement, generous gestures towards the teacher, and frequent smiling, contrasting with previous instances of math anxiety during learning sessions. Furthermore, the results indicate that RME facilitates comprehension of mathematical concepts and fosters understanding of the intersection between mathematics and Islamic life among minority groups, as detailed in this article.